Judicial review reform: avoiding effective review through procedural means?. (2nd January 2016) - McIntyre, Joe; Neudorf, Lorne
ABSTRACT: From the starting point that public officials and specialist administrative agencies affect most areas of economic and social life in the modern 'administrative state', the authors highlight rule of law concerns that have been raised with recent English reforms to restrict the availability of access to a reviewing court through changes to the judicial review procedure. The authors consider this argument in light of comparative studies of the existing law and recent reforms in Australia, Canada, and England and Wales. This comparison provides evidence of much tighter restrictions on time limits for bringing an application for judicial review as opposed to litigation in other subject matters. The authors also situate the focus on judicial review procedure within the broader trend of proceduralism in civil litigation. The authors conclude that while there is a legitimate need for established procedures to control the judicial process and ensure efficiency, cost-effectiveness, and broader public interests, overbearing procedural reforms risk accessible and effective judicial review of public agencies and officials, which can impair the principle of legality in that all public decision-making must be held to established legal standards.